Kant's Philosophy of the Unconscious - Giordanetti, Piero; Pozzo, Riccardo; Sgarbi, Marco (Berlin/Boston De Gruyter)
In the 20th century, the role of the unconscious in Kant`s philosophy has been in great part neglected by Kant scholars. Nevertheless, the unconscious, the other of consciousness, is a key problem of the critical philosophy. The purpose of the volume is to fill a substantial gap in Kant research and to offer a complete survey of the topic in different areas of research, such as history of philosophy, philosophy of mind, aesthetics, moral philosophy, and anthropology.
English
Keywords: Philosophy; History of Philosophy; Apperception; Cognition; Consciousness; Critique of Pure Reason; Felix Mendelssohn; Gottfried Wilhelm Leibniz; Immanuel Kant; Intuition